2010
DOI: 10.1007/s11250-010-9761-5
|View full text |Cite
|
Sign up to set email alerts
|

Milk producers’ awareness of milk-borne zoonoses in selected smallholder and commercial dairy farms of Zimbabwe

Abstract: A cross-sectional questionnaire-based study was conducted to assess milk producers' awareness of milk-borne zoonoses in selected smallholder and commercial dairy farms of Zimbabwe. The questionnaire was designed to obtain information on dairy breeds, milk production, dairy farmers' knowledge and awareness of zoonoses with particular emphasis on milk-borne zoonoses and farmers' behavioural practices that may lead to increased risk of milk-borne zoonoses transmission. A total of 119 dairy farmers were interviewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
27
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 15 publications
(19 reference statements)
15
27
0
1
Order By: Relevance
“…However, knowledge on rabies was found to be higher than other zoonotic diseases and this fact also conjoins with this study. Similar results were also reported by a researcher [22] where they concluded that 87% small scale holders had low to fair level of knowledge regarding zoonosis. This low and medium level of awareness could be due to remoteness, lack of health facilities, poor extension services, low training status on rearing and handling of animals, and low literacy rate which have been reported as major contributors to the low level of awareness among dairy farmers [23].…”
Section: Awareness and Knowledge Of Livestock Farmers Toward Zoonoticsupporting
confidence: 87%
“…However, knowledge on rabies was found to be higher than other zoonotic diseases and this fact also conjoins with this study. Similar results were also reported by a researcher [22] where they concluded that 87% small scale holders had low to fair level of knowledge regarding zoonosis. This low and medium level of awareness could be due to remoteness, lack of health facilities, poor extension services, low training status on rearing and handling of animals, and low literacy rate which have been reported as major contributors to the low level of awareness among dairy farmers [23].…”
Section: Awareness and Knowledge Of Livestock Farmers Toward Zoonoticsupporting
confidence: 87%
“…It has been reported elsewhere that this human behavior is partly influenced by lack of awareness ( Mosalagae et al 2011), perceptions, and attitude (Opare et al 2000, Shirima et al 2003, John et al 2008, and/or misconceptions (Webb 2003) about zoonoses. Hence, it is important for cattle owners to acquire a certain degree of awareness of livestock diseases in their areas, the risks they pose, and possible transmission routes to humans, if they are to make informed decisions on diseases suspected to have zoonotic potential.…”
mentioning
confidence: 93%
“…According to (Chenyambuga et al, 2010) the currently held concept of TBDs control has to be revised and should consider the indigenous knowledge of livestock keepers. Literature search on the involvement of farmers in studying the epidemiology of diseases in Zimbabwe revealed that only a few studies had been conducted (Chikerema et al, 2013;De Garine-Wichatitsky et al, 2013;Mosalagae et al, 2011;Pfukenyi et al, 2010) and none of these have directly looked at TBDs. This is despite the importance placed on TBDs by the government Department of Veterinary Services in the country.…”
Section: Introductionmentioning
confidence: 99%